A new striking dendrobatid frog (Dendrobatidae: Aromobatinae, Aromobates) from the Venezuelan Andes - Barrio-Amorós, César L.; Rivero, Ramón; Santos, Juan C. (Zootaxa, 2011)
A new striking cloud frog of the genus Aromobates is described from the northwestern portion of the Cordillera de Merida in Venezuela. The new species is unique in several aspects, and its inclusion in Aromobates is supported by molecular analyses. This Aromobates is characterized by the presence of dark dorsolateral stripes, absence of pale dorsolateral, oblique lateral and ventrolateral stripes. Furthermore, it is the only non-aposematic Aromobates having dark to emerald green in life on dorsal surfaces and a highly ornamented pattern at both dorsal and ventral sides. This species is known from a single population in Carache (Trujillo State, Venezuela). Its population, although limited apparently to a small area, seems relatively abundant at the type locality and surroundings.